"Connectedness" between people with intellectual disabilities and challenging behaviour and support staff: Perceptions of psychologists and support staff. (March 2023) - Tournier, T; Hendriks, AHC; Jahoda, A; Hastings, RP; Embregts, PJCM
The tacit practical knowledge of psychologists and support staff to foster a real connection between support staff and people with intellectual disabilities and challenging behaviour was explored. Therefore, six dyads comprising individuals with intellectual disabilities and challenging behaviour and their support staff were video recorded during joint engagement in an activity. To tap into the implicit knowledge of professionals about when staff have 'a real connection' with a person with an intellectual disability, 10 psychologists and 10 support staff were asked to pinpoint these moments in the pre-recorded video compilation. They also shared their interpretations about what they considered to be a real connection. The results displayed that participants designated real connections as occurring when they noticed concrete interactions taking place. Based on thematic analysis of the data, four themes were identified that encapsulated what professionals deemed to be a real connection. In conclusion: joint engagement in an activity appears to be a context that fosters opportunities for real connection. Furthermore, support staff should adopt a sensitive attitude and create a safe atmosphere, to establish real connections.